Developing community technology: A profile website for SDI Miftahus Sholihin - Hendro Priyatman; Seno Darmawan Panjaitan; Hilda Hilda; Eka Kusumawardhani; Leonardus Sandy Ade Putra (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
The Community Service Program titled "Developing Community Technology: A Profile Website for SDI Miftahus Sholihin" aims to address various challenges associated with school accreditation through the utilization of information and communication technology (ICT). The program's objectives are to enhance the quality of education and facilitate better access to information. It entails the design, development, and management of a profile website for SDI Miftahus Sholihin, alongside training sessions focused on website management and promotion strategies. These efforts are geared towards achieving improvement targets in school accreditation. The program timeline spans six months, encompassing phases of preparation, coordination, website development, training, and evaluation. Anticipated outcomes include heightened information quality and accessibility pertaining to school-related matters, as well as the enhancement of website management skills among school staff. Ultimately, the program aspires to elevate the educational quality of SDI Miftahus Sholihin, foster greater community engagement in educational initiatives, and facilitate the attainment of higher accreditation standards for the school.